2017
DOI: 10.1371/journal.pone.0169579
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated Expression of Mitochondrial Proteins Mfn2 and Bcnl3L in Placentae from Sheep Somatic Cell Nuclear Transfer (SCNT) Conceptuses

Abstract: In various animal species, the main cause of pregnancy loss in conceptuses obtained by somatic cell nuclear transfer (SCNT) are placental abnormalities. Most abnormalities described in SCNT pregnancies (such as placentomegaly, reduced vascularisation, hypoplasia of trophoblastic epithelium) suggest that placental cell degeneration may be triggered by mitochondrial failure. We hypothesized that placental abnormalities of clones obtained by SCNT are related to mitochondrial dysfunction. To test this, early SCNT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The strategies put forth to improve its efficiency have had a negligible effect in farm animals, and minimal advancements have been achieved only in the mouse. Moreover, the unexpected mitochondrial dysfunctions in cloned embryos, reported for the first time by our group (Czernik et al, 2017), adds a further level of complication to cloning research. Clearly, it appears unlikely that all the biological constraints impairing cloning could be removed by a single treatment/protocol.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…The strategies put forth to improve its efficiency have had a negligible effect in farm animals, and minimal advancements have been achieved only in the mouse. Moreover, the unexpected mitochondrial dysfunctions in cloned embryos, reported for the first time by our group (Czernik et al, 2017), adds a further level of complication to cloning research. Clearly, it appears unlikely that all the biological constraints impairing cloning could be removed by a single treatment/protocol.…”
Section: Discussionmentioning
confidence: 84%
“…Additionally, it has been shown that low expression of MFN2 in human placentas is associated with mitochondrial damage in placental cells and unexplained miscarriage (Pang et al, 2013). Recently, Czernik et al, (2017) reported that deregulated expression of mitochondrial proteins (MFN2 and BCNL3L) cause abnormalities in early pregnancy placenta in sheep. Abnormalities were mainly presented as damaged and malformed mitochondria, as well as swollen endo-plasmic reticula (Czernik et al, 2017).…”
Section: Mitochondria In Scnt Placentamentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the already existing complications, the unexpected mitochondrial dysfunctions in cloned embryos complicate the cloning process. Thus, it reduces the success rate ( Czernik et al, 2017 ). Several initiatives have, therefore, been implemented to boost the effectiveness of SCNT.…”
Section: Animal Cloningmentioning
confidence: 99%
“…Placental research by RNA-seq for abortion and aberrant pregnancy in livestock mainly focused on early gestation or postnatal. [6][7][8][9] little about which However, few studies have looked at the placenta during the third trimester, when large quantity of SCNT fetal abortion occur.…”
Section: Introductionmentioning
confidence: 99%